2008
DOI: 10.1093/nar/gkn209
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of structure-free DNA with pseudo-complementary properties

Abstract: Long single-stranded DNAs and RNAs possess considerable secondary structure under conditions that support stable hybrid formation with oligonucleotides. Consequently, different oligomeric probes can hybridize to the same target with efficiencies that vary by several orders of magnitude. The ability to enzymatically generate structure-free single-stranded copies of any nucleic acid without impairing Watson–Crick base pairing to short probes would eliminate this problem and significantly improve the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…1 H NMR (DMSO-d 6 , 300 MHz) δ ppm: 2.0-2.1 (m, 1H, CH 2 -2 0 ); 2.1-2.3 (m, 1H, CH 2 -2 00 ); 3.5-3.7 (m, 2H, CH 2 -5 0 and 5 00 ); 3.7-3.8 (m, 1H, CH-4 0 ); 4.1-4.2 (m, 1H, CH-3 0 ); 5.5-5.8 (m, 2H, OH-3 0 and OH-5 0 ); 6.01 (t, 1H, CH-1 0 , 3 J H1 0 -H2 0 = 3 J H1 0 -H2 00 = 6.0 Hz); 7.2-7.6 (2 br s, 2H, NH 2 ); 8.71 (s, 1H, CH-6). 13 47 5-Carbamoyl-2 0 -deoxycytidine (2a). Compound 14 (0.210 g, 0.83 mmol) in water (60 mL) was treated with a 1 M NaOH solution (6 mL).…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR (DMSO-d 6 , 300 MHz) δ ppm: 2.0-2.1 (m, 1H, CH 2 -2 0 ); 2.1-2.3 (m, 1H, CH 2 -2 00 ); 3.5-3.7 (m, 2H, CH 2 -5 0 and 5 00 ); 3.7-3.8 (m, 1H, CH-4 0 ); 4.1-4.2 (m, 1H, CH-3 0 ); 5.5-5.8 (m, 2H, OH-3 0 and OH-5 0 ); 6.01 (t, 1H, CH-1 0 , 3 J H1 0 -H2 0 = 3 J H1 0 -H2 00 = 6.0 Hz); 7.2-7.6 (2 br s, 2H, NH 2 ); 8.71 (s, 1H, CH-6). 13 47 5-Carbamoyl-2 0 -deoxycytidine (2a). Compound 14 (0.210 g, 0.83 mmol) in water (60 mL) was treated with a 1 M NaOH solution (6 mL).…”
Section: Methodsmentioning
confidence: 99%
“…19 Reverse phase DCVC was performed using the same procedure, with the modifications that Waters RP 18 (0.055-0.105 mm) silica gel was employed, and the compound was applied on the column dissolved in a small amount 60:40, water:acetonitrile. 1 H and 13 C NMR spectra were recorded on a Varian 400 MHz or a Bruker Avance 300 Fourier transform spectrometer using an internal deuterium lock. Solvents were Compound 2 (1.48 g, 2.44 mmol) was stirred in trifluoroacetic acid (45 ml) at 0°C for 6½ h. The solution was evaporated to dryness in vacuo and co-evaporated once with toluene (30 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Such pseudo-complementary oligonucleotides are of major interest for sequence specific targeting of duplex DNA by double duplex invasion strategies, [1][2][3][4][5][6][7][8][9][10] and as efficient sequence palindromic (self-complementary) hybridization probes for hairpin forming in RNA targets. [11][12][13] Previous work has shown that PNA or DNA oligomers with pseudo-complementary properties are obtained upon substitution of A-T bases by 2,6-diaminopurine (D)-thiouracil (sU) (or thiothymine) bases, whereas analogous pseudo-complementary G-C base pairs have proven elusive. 13 In order to approach an effective pseudo complementary G-C base pair we considered that the unnatural nucleobases N6-methoxy-2,6-diaminopurine (previously described in a DNA context), 14 and N4-benzoylcytosine 15 could indeed constitute such a pair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the pcDNA is hybridised to normal DNA it is significantly more thermally stable than even the corresponding DNA duplex. 182 Several different modified nucleotides were also examined to find pcDNA equivalents for the G:C base pair, the most promising being either the 7-nitro-7-deazaguanine and 2-thiocytosine, 308 or 7-alkyl-7deazaguanine and N4-alkylcytosine 309 analogues.…”
Section: Oligonucleotides Containing Modified Sugarsmentioning
confidence: 99%